Evaluating The Role of Individualized Homoeopathic Treatment in the Management of Urolithiasis: A Case Study - Dr. Hiral K. Trivedi; Dr. Jignesh Patel (The Bioscan, 2025)
The modern lifestyle and chaotic eating habits is a part of today's life, which has given rise to many diseases among these diseases one is renal stone. Modern medicine relies mostly on surgery for its treatment. It is a common belief in the conventional system in medical science that stones greater than 7 mm usually need to be removed surgically. Renal calculi are hard deposits of minerals and acid salts that stick together in concentrated urine. Surgical intervention is not always mandatory, because there are evidence-based documentations are available where homoeopathy act marvellously in dissolution and expulsion of bigger stones. A patient of urolithiasis reported in a clinical setting. Detailed case taking of the patient was done and individualized homoeopathic medicine was prescribed on the basis of totality of symptoms after repertorization done by Homoeopathic Medical Repertory by Dr. Robin Murphy. Lycopodium was prescribed as the individualized medicine. The clinical status of the patient was analyzed by ultrasonography imaging. constitutional approach of yielded encouraging results. There was symptomatic relief of the patient and post-treatment ultrasonography showed no calculus after homoeopathic interventions. KEYWORDS Urolithiasis, Homoeopathy, Lycopodium, Urolithiasis Symptoms Score (USS) Scale.